Kapasitas Individu Masyarakat Desa dalam Pengembangan Ekowisata di Desa Sambirata Kecamatan Cilongok Kabupaten Banyumas - Sabila Tri Amelia; Suwarsito Suwarsito; Esti Sarjanti (UM Purwokerto Press, 2022)
Ecotourism is a form of travel to natural areas carried out with the aim of conserving the environment and preserving the life and welfare of local residents [1]. Sambirata village is located in the highlands with a hilly topography. The natural and socio-cultural conditions of rural communities have their own ecotourism appeal. This study aims to determine the individual capacity of the Sambirata Village community in the development of ecotourism. Individual community is the main element in the development of ecotourism, the quality of individual communities will determine the success of an ecotourism activity. This study uses a survey method by taking data directly on samples in the field using a questionnaire sheet, to 23 respondents with random sampling techniques in the community around the Bukit Gondang ecotourism area (RT 01 RW 05). The data needed in this study include knowledge and understanding of ecotourism principles, management of tourist attractions, pioneering ecotourism potential, services to tourists and the level of community education. Data analysis used quantitative and qualitative descriptive. The results of this study indicate that the individual capacity of the Sambirata village community in developing ecotourism is low with a percentage of 69.57%. With minimal knowledge and community participation in ecotourism development.